2013
DOI: 10.1007/s13353-013-0140-6
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of genetic variability and phylogenetic analysis of selected Czech and French strains of rabbit haemorrhagic disease virus (RHDV)

Abstract: The objective of this study was to analyse the genetic variability and phylogenetic analysis of six strains of rabbit haemorrhagic disease virus (RHDV), including four Czech strains (CAMPV-351, CAMPV-561, CAMPV-562, CAMPV-558) and two French strains (Fr-1, Fr-2), on the basis of a fragment of the VP60 capsid structural protein-coding gene N-terminal region. The results of our own studies were compared to 26 RHDV strains obtained from GenBank. The analysis of the genetic variability of six RHDV strains indicate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 42 publications
(109 reference statements)
0
5
0
Order By: Relevance
“…The study showed the lack of amplification of STR 2012 genetic material with P1 primer (5182-5201) from the C-terminus of the RHDV RdRp polymerase gene. The primer set P1/P2, originally proposed by Guittré et al (21), has been used for many years in many laboratories for routine amplification of classic RHDV strains, including HA-negative phenotypic variants (23,26). Similar difficulties were encountered in the amplification of cDNAs of the samples L1-L6 with the pair of primers N3-N4 encoding the N-terminal part of the VP60 gene.…”
Section: Discussionmentioning
confidence: 99%
“…The study showed the lack of amplification of STR 2012 genetic material with P1 primer (5182-5201) from the C-terminus of the RHDV RdRp polymerase gene. The primer set P1/P2, originally proposed by Guittré et al (21), has been used for many years in many laboratories for routine amplification of classic RHDV strains, including HA-negative phenotypic variants (23,26). Similar difficulties were encountered in the amplification of cDNAs of the samples L1-L6 with the pair of primers N3-N4 encoding the N-terminal part of the VP60 gene.…”
Section: Discussionmentioning
confidence: 99%
“…A sequence from European brown hare syndrome virus was used as an out‐group to root the tree. The best‐fitting evolutionary model was determined based on our previous knowledge and available information (Esteves et al., ; Hukowska‐Szematowicz, Tokarz‐Deptula, & Deptula, ) on genome dynamics and evolution of rabbit haemorrhagic disease viruses such as the pattern of nucleotide substitution and the variability of substitution rates among sites in RHDV genome. By performing an initial phylogenetic analysis using the neighbour‐joining method in combination with variation of models, the Tamura–Nei model was selected for the final analysis.…”
Section: Methodsmentioning
confidence: 99%
“…3) is of considerable interest, since this feature is not typical for most viruses. For example, rabbit hemorrhagic disease virus (RHDV) strains tend to cluster geographically [27], which was not observed in this case. These results, as well as others from a number of previous studies [13], in fact highlight the circulation of several strains in the same geographical location.…”
Section: Discussionmentioning
confidence: 68%